Pulse foods : processing, quality and nutraceutical applications - Gowen, Aoife; McKenna, Brian; Tiwari, Brijesh K. (Elsevier/Academic Press, 2011)
Pulses are nutritionally diverse crops that can be successfully utilized as a food ingredient or a base for new product development. They provide a natural food grade ingredient that is rich in lysine, dietary fiber, complex carbohydrates, protein and B-vitamins suggesting that pulses can provide a variety of health benefits such as reducing heart disease and diabetes. Interest in the use of pulses and their ingredients in food formulations is growing and several factors are contributing to this drive. Pulse Foods: Processing, Quality and Nutraceutical Applications is the first book to provide up-to-date information on novel and emerging technologies for the processing of whole pulses, techniques for fractionating pulses into ingredients, their functional and nutritional properties, as well as their potential applications, so that the food industry can use this knowledge to incorporate pulses into new food products. First reference bringing together essential information on the processing technology of pulses Addresses processing challenges relevant to legume and pulse grain processors Delivers insights into the current state-of-art and emerging processing technologies In depth coverage of developments in nutraceutical applications of pulse protein and carbohydrate based foods